GRAMMAR OF THE ALTAI LANGUAGE, THE BEGINNING OF THE GRAMMATICAL STRUCTURE OF THE KYRGYZ LANGUAGE (comparison of case ending affixes) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The fact that the Kyrgyz Language is an ancient Ianguage has already been established and clarified based on factual materials. The grammar compiled from them by Altai missionaries, informs the structure of the grammar of the Kyrgyz Language. After all, when we look at the cases and their affixes, we understand where the Kyrgyz Language originated from. The article, based on comparison, examines the category of cases in Altai and modern Kyrgyz Languages.
Keywords: cases, Altai missionaries, grammatical process, standard scheme, nominative, genitive, dative, accusative, locative, original